Inverse Scattering Problem for One-Dimensional Schrödinger Equation with Discontinuity Conditions - Huseynov, H.M.; Osmanli, J.A. (Журнал математической физики, анализа, геометрии, 2013)
The direct and inverse scattering problems for the second order ordinary differential equation on the whole axis with discontinuity conditions at some point are considered. Рассмотрены прямые и обратные задачи рассеяния для обыкновенного дифференциального уравнения второго порядка на всей оси с условиями разрыва в некоторой точке.